Deep Inferior Epigastric Perforators Topography for “Island Transverse Rectus Abdominis Musculocutaneous Flap” in Breast Reconstruction - Tae Hyun Kim; Seong Heum Jeong; Hee Chang Ahn (Archives of Plastic Surgery, 2023)
Background The Island transverse rectus abdominis musculocutaneous (TRAM) flap is well vascularized with very reliable blood flow, because all perforators of the zone I are included when it is harvested. The number of perforators, topographic mapping, and their relationship with reconstructed outcomes were investigated.